2019
DOI: 10.1007/s42452-019-0235-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analysis of gradient effect on the dynamic performance of three-wheeled vehicle system using Simscape

Abstract: In India, three-wheeled electric vehicles are one of the important modes of public transport in congested areas. The gradient is an important factor that affects the dynamic performance of the vehicle. The proposed work presents an extensive analysis of the gradient effects on the dynamic performance of a three-wheeled solar electric vehicle. Firstly, we have designed the physical vehicle model of three-wheeled using Simscape ® environment tool. The generated torque from "ideal torque source" block is transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The identification of actual residues of predicted active site, involved in binding with the ligand of accurate conformation has been answered by molecular docking task. The available conformers of selected ligands obtained after ligand preparation were docked with the modeled protein [44,45]. From the post dock analysis, it was observed that as compared to all eleven ligands, the compound folic acid showed highest interaction with the protein (Glide Score: − 9.980503 kcal/ mol) ( Table 1).…”
Section: Active Site Prediction and Molecular Dockingmentioning
confidence: 99%
“…The identification of actual residues of predicted active site, involved in binding with the ligand of accurate conformation has been answered by molecular docking task. The available conformers of selected ligands obtained after ligand preparation were docked with the modeled protein [44,45]. From the post dock analysis, it was observed that as compared to all eleven ligands, the compound folic acid showed highest interaction with the protein (Glide Score: − 9.980503 kcal/ mol) ( Table 1).…”
Section: Active Site Prediction and Molecular Dockingmentioning
confidence: 99%
“…The necessary tractive torque for three-wheeled e-vehicle is provided by the e-propulsion system [17]. E-propulsion system converts the electric energy of batteries into mechanical power [18].…”
Section: Introductionmentioning
confidence: 99%
“…The engine in both studies is used as the main range enhancer for the electric vehicle. Furthermore, Waseem et al present modeling of a three-wheeled electric vehicle and focus on the analysis of the gradient effect on the vehicle's dynamic performance [16]. Targosz et al also modeled an electric vehicle, which focuses on electric racing cars [17].…”
Section: Introductionmentioning
confidence: 99%